Adobe Photoshop Cs In 10 Simple Steps Or Less - Schmitt, Christopher (Wiley Publishing, 2011)
If you are looking to create exciting Web graphics and need to define and edit images quickly and easily, then this book is for you-whether you're new to Adobe's latest graphics editing software or you need a refresher on Photoshop's wide range of resources. Open the book and you'll discover clear, easy-to-follow instructions for more than 250 key Photoshop tasks, each presented in ten quick steps-or less. Easy - to - navigate pages, lots of screen shots, and to-the-point directions guide you through every common (and not so common) Photoshop challenge-and help you get more done in less time. * Each solution is ten steps-or less-to help you get the job done fast * Self-contained two-page spreads deliver the answers you need-without flipping pages * A no-fluff approach focuses on helping you achieve results * A resource packed with useful and fun ways to get the most out of Photoshop cs * Make it simple and get productive fast! - find full-color images and links to resources, downloads, and companion and plug-in software on this book's Web site